Essential Tremor Prevalence is Low in the Druze Population in Northern Israel. (22nd March 2012) - Aharon-peretz, Judith; Badarny, Samih; Ibrahim, Raphiq; Gershoni-baruch, Ruth; Hassoun, Gamal
Background: Essential tremor (ET) and Parkinson's disease (PD) are probably the most common movement disorders. As ethnic differences have been reported in ET, we designed the present study to evaluate the prevalence of ET and that of Parkinson's disease (PD) in the Druze villages of northern Israel. Methods: A two-phase, door-to-door survey was undertaken. Residents aged ≥51 years who agreed to participate and answered "yes" to tremor or PD-related screening questions and 3% of subjects who screened negative were evaluated. Diagnostic criteria for ET were similar to those used in Sicilian and Spanish studies. PD was diagnosed according to Gelb's criteria. Results: The target population consisted of 9, 086, the study cohort of 3, 980 residents. Tremor was observed in 36 subjects. In 27, the tremor fully met the criteria for ET. The prevalence of ET (age ≥65) was 1.49% (95% CI 0.91–2.07%). PD was diagnosed in 23 subjects. The prevalence of PD (age ≥65) was 1.13 (95% CI 0.62–1.64%). Leucine-rich repeat protein kinase 2 (G2019S mutation) was evaluated in subjects diagnosed with tremor PD and those screened for assessment of the validity of the questionnaire. None carried the mutation. Discussion: The prevalence of ET in the Druze population is low and similar to the prevalence of PD.